Design and Analysis of Lagrangian Algorithm for Power Flow System using Renewable Energy Resources - Subramani Rajamanickam; Vijayalakshmi C (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper mainly deals with the implementation of an Lagrangian Relaxation (LR) technique through a Supervisory Control and Data Acquisition (SCADA) system. Maintaining Power Station is not an easy task which to achieve its demand such as regulating inputs monitoring energy losses. In this paper we have introduced novel SCADA based decentralized approach to minimize the loss of the system and optimize the total generation cost. Due to the nonlinearities of Electricity demand and scheduling time, the problem is not solvable with the usual optimization techniques. For getting appropriate solution LR technique has been formulated as a nonlinear programming problem with respect to optimal energy constraints. Based on the numerical calculations and graphical representations the renewable energy sources are optimally allocated in individual and hybrid configurations, which leads to effective production.